2021
DOI: 10.1021/jacs.1c09828
|View full text |Cite
|
Sign up to set email alerts
|

Photoenzymatic Synthesis of α-Tertiary Amines by Engineered Flavin-Dependent “Ene”-Reductases

Abstract: 𝛼-tertiary amines are a common motif in pharmaceutically important molecules but are challenging to prepare using asymmetric catalysis. Here, we demonstrate engineered flavin-dependent 'ene'-reductases (EREDs) can catalyze radical additions into oximes to prepare this motif. Two different EREDs were evolved into competent catalysts for this transformation with high levels of stereoselectivity. Mechanistic studies indicate that the oxime contributes to the enzyme templated CTcomplex formed between the substrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…They later extended the strategy of photoexcitation to flavoenzymes and discovered photoexcitation of an alkene-tethered α-chloroamide-flavin EDA complex in ene-reductases (EREDs) permitted an asymmetric reductive cyclization for the production of five- to eight-membered lactams with a β- or γ-stereocenter (Figure B) . Very recently, they expanded the scope of the reductive cyclization to chiral tertiary amine synthesis by altering the radical acceptor from a tethered CC double bond to an oxime . They further used an intramolecular aromatic ring to trap the photogenerated α-amido carbon radicals when developing a stereoselective redox neutral cyclization to create chiral oxindoles (Figure C) .…”
Section: Elucidation Of New Photoreactivity Within Cofactor-dependent...mentioning
confidence: 99%
“…They later extended the strategy of photoexcitation to flavoenzymes and discovered photoexcitation of an alkene-tethered α-chloroamide-flavin EDA complex in ene-reductases (EREDs) permitted an asymmetric reductive cyclization for the production of five- to eight-membered lactams with a β- or γ-stereocenter (Figure B) . Very recently, they expanded the scope of the reductive cyclization to chiral tertiary amine synthesis by altering the radical acceptor from a tethered CC double bond to an oxime . They further used an intramolecular aromatic ring to trap the photogenerated α-amido carbon radicals when developing a stereoselective redox neutral cyclization to create chiral oxindoles (Figure C) .…”
Section: Elucidation Of New Photoreactivity Within Cofactor-dependent...mentioning
confidence: 99%
“…Beispielsweise sind α-tertiäre Amine durch stereoselektive radikalische Addition an Oxime und anschließende chemische Reduktion der gebildeten Hydroxylamine zugänglich (Abbildung c). 6) In vielen Fällen optimierten gezielte Mutationen im aktiven Zentrum die Effizienz und Selektivität der photoenzymatischen Katalyse. Daher arbeiten immer mehr Forschungsgruppen an der gerichteten Evolution von Photoenzymen.…”
Section: Rational Designte Photoenzymeunclassified
“…While the hallmark of this reactivity is high enantioselectivity, we recognized that preferential formation of the lactam product would be synthetically valuable. [21][22][23][24][25][26][27][28] We attribute the high level of product selectivity to the enzyme selectively binding the cis-amide isomer, preorganizing the substrate for cyclization. 21 We found that a small collection of ERED homologues can facilitate different amide radical cyclization.…”
Section: Cluster Synlettmentioning
confidence: 99%